Integrating Mechatronics In Project-based Learning Of Malaysian High School Students And Teachers - Flavia Tauro; Youngsu Cha; Mohammad Sattar Rasul; Kamisah Osman; Lilia Halim; Dominick Dennisur; Ben Esner; Maurizio Porfiri; Faszly Rahim (SAGE Publication, 2024)
Indexed by Scopus